2020
DOI: 10.1093/jxb/eraa115
|View full text |Cite
|
Sign up to set email alerts
|

Rice F-bZIP transcription factors regulate the zinc deficiency response

Abstract: The F-bZIP transcription factors bZIP19 and bZIP23 are the central regulators of the zinc deficiency response in Arabidopsis, and phylogenetic analysis of F-bZIP homologs across land plants indicates that the regulatory mechanism of the zinc deficiency response may be conserved. Here, we identified the rice F-bZIP homologs and investigated their function. OsbZIP48 and OsbZIP50, but not OsbZIP49, complement the zinc deficiency-hypersensitive Arabidopsis bzip19bzip23 double mutant. Ectopic expression of OsbZIP50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 36 publications
9
79
3
Order By: Relevance
“…Among these, the TFs HvbZIP56 and HvbZIP62 could restore the growth of bzip19 and bzip23 double mutant of Arabidopsis under Zn deficiency condition (Nazri et al, 2017). Recently, Lilay et al (2020) identified and characterized three bZIP TFs in rice such as OsbZIP48, OsbZIP49, and OsbZIP50. The OsbZIP48 and OsbZIP50 complemented the Arabidopsis double mutant (bzip19/bzip23) under Zn deficient condition but the OsbZIP49 does not compliment the Arabidopsis double mutant (bzip19/bzip23) (Lilay et al, 2020).…”
Section: Regulation Of Zip Transporters In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the TFs HvbZIP56 and HvbZIP62 could restore the growth of bzip19 and bzip23 double mutant of Arabidopsis under Zn deficiency condition (Nazri et al, 2017). Recently, Lilay et al (2020) identified and characterized three bZIP TFs in rice such as OsbZIP48, OsbZIP49, and OsbZIP50. The OsbZIP48 and OsbZIP50 complemented the Arabidopsis double mutant (bzip19/bzip23) under Zn deficient condition but the OsbZIP49 does not compliment the Arabidopsis double mutant (bzip19/bzip23) (Lilay et al, 2020).…”
Section: Regulation Of Zip Transporters In Plantsmentioning
confidence: 99%
“…Recently, Lilay et al (2020) identified and characterized three bZIP TFs in rice such as OsbZIP48, OsbZIP49, and OsbZIP50. The OsbZIP48 and OsbZIP50 complemented the Arabidopsis double mutant (bzip19/bzip23) under Zn deficient condition but the OsbZIP49 does not compliment the Arabidopsis double mutant (bzip19/bzip23) (Lilay et al, 2020).…”
Section: Regulation Of Zip Transporters In Plantsmentioning
confidence: 99%
“…The basic leucine zipper (bZIP) transcription factors are involved in a plethora of plant biological processes and responses, including signal transduction [ 6 , 13 ], tissue differentiation [ 13 ], hormone signaling [ 14 ], nutrition [ 15 ], and stress tolerance [ 6 , 16 ]. For this reason, evaluating the potential nSe-associated alteration in the bZIP transcription factor was also one of the aims of this study.…”
Section: Introductionmentioning
confidence: 99%
“…To date, plenty of literatures show that bZIPs regulate plant tolerances to various abiotic stresses, such as low temperature, drought, high salt, nitrogen deficiency, zinc deficiency time ( Lilay et al, 2020 ; Ueda et al, 2020 ). Besides, there are many reports reveal that flavonoids participate in various stress responses.…”
Section: Discussionmentioning
confidence: 99%